Supersymmetric Quantum Mechanics Formalism in a Modeling for Protein Folding - Drigo Filho, E. [UNESP]; Chahine, J. [UNESP]; Araujo, M. T.; Ricotta, R. M. [UNESP] (IOP Publishing, 2023)
Recently, a mathematical method was developed to analyze the kinetics of the protein folding process, considering it as a diffusion process described by the Fokker-Planck equation and its solution, the time-dependent probability density. This work presents the main points of the methodology, based on the application of the algebraic formalism of Supersymmetric Quantum Mechanics associated with the variational method, to analyze the symmetric tri-stable free energy potential function that describes the unfolded and folded states, as well as an intermediate state of the protein.